PERLINDUNGAN HUKUM BAGI PEMOHON KREDIT DENGAN MENGACU PADA ASAS KESEIMBANGAN ANTARA PELAKU USAHA (BANK) DAN KONSUMENNYA (PEMOHON KREDIT) - Ni Luh Putu Sri Suryaningsih (University of Udayana, 2012)
Banking institutions as one of the financial institutions have a strategic rolein supporting the economic life of a country. Banking institutions meant hereas an intermediary of the parties who have surplus funds to the lack of funds.Banking activities that provide services on the economic sector that do not inspite of the risks that could harm the banks themselves and the customer.Relationship between the bank and the customer is bound to a creditagreement unnoticed by the debtor of his rights is often overlooked by thebank. Guaranteeing the law protection and law certainty for the debtorslosing for such unilateral, the regulations of consumer protection, therefore,have important functions. The type of research used in this paper is thenormative legal research. This research moved from the inclusion of thestandard clause that would open up opportunities for businesses, especiallybanks to position the client, in this case the credit applicant, to be weakerthan the bank.